NATO and the Ukraine crisis: Collective securitisation. (5th December 2016) - Sperling, James; Webber, Mark
Abstract: In securitisation theory (ST) little attention has been paid to how actors undertake securitisation collectively. The empirical focus of that theory has also, paradoxically, neglected the military-strategic sector and with it regional security organisations like NATO. Such an oversight is worth correcting for three reasons. First, NATO is constantly engaged in securitisation across a range of issues, a process that reflects an underappreciated recursive interaction between the Alliance and its member states. Second, the Ukraine crisis has resulted in Russia being explicitly identified as a source of threat and so has triggered a successful collective (re)securitisation by the Alliance. Third, a framework that demonstrates NATO's standing as a securitising actor has potential relevance to other regional security organisations. This article discusses and amends ST in service of an approach that permits securitisation by actors other than the state, in this case NATO. A model of collective securitisation is presented and then applied empirically to the post-Cold War desecuritisation of Russia and its subsequent resecuritisation following the annexation of Crimea. The implications of resecuritisation for the emergence of a self-reinforcing security dilemma in NATO-Russia relations are also considered.